2022
DOI: 10.4103/eus-d-21-00244
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of endoscopic anterior fundoplication with a novel ultrasonic surgical endostapler for gastroesophageal reflux disease: Six-month results from a multicenter prospective trial

Abstract: Background and Objectives: Endoscopic therapy is an option for the treatment of refractory gastroesophageal reflux disease (GERD). We aimed to evaluate the efficacy and safety of transoral incisionless fundoplication with the Medigus ultrasonic surgical endostapler (MUSE™) for refractory GERD. Materials and Methods: Patients with 2 years of documented GERD symptoms and at least 6 months of proton-pump inhibitors (PPIs) therapy were enrolled in four medical centers from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…40,52 In two prospective single-arm studies, this technique demonstrated therapeutic efficacy (improved GERD-HRQL and discontinuation of daily PPI) with a relatively safe profile at 6 months. 52,53 In another study comprising 34 patients with GERD, of the 20 subjects who underwent the MUSE procedure and completed follow-up, 70% experienced significant improvement (50% reduction in GERD-related symptom scores) in GERD-HRQL, 65% in heartburn symptoms, 75% in regurgitation symptoms, and 65% stopped PPI therapy at 12 months post-procedure. 54…”
Section: Medigus Ultrasonic Surgical Endostaplermentioning
confidence: 99%
“…40,52 In two prospective single-arm studies, this technique demonstrated therapeutic efficacy (improved GERD-HRQL and discontinuation of daily PPI) with a relatively safe profile at 6 months. 52,53 In another study comprising 34 patients with GERD, of the 20 subjects who underwent the MUSE procedure and completed follow-up, 70% experienced significant improvement (50% reduction in GERD-related symptom scores) in GERD-HRQL, 65% in heartburn symptoms, 75% in regurgitation symptoms, and 65% stopped PPI therapy at 12 months post-procedure. 54…”
Section: Medigus Ultrasonic Surgical Endostaplermentioning
confidence: 99%
“…Current treatments for ES encompass various modalities, including drug therapy, surgical interventions, endoscopic esophageal dilation, and endoscopic stent placement, among others ( Sehgal and Sami, 2021 ). Pharmacological treatment entails the administration of proton pump inhibitors (PPI) for managing GERD ( Peng et al, 2023 ). Additionally, endoscopy-guided infusion of adrenocorticotropic and cytotoxic drugs into the stenosis site serves to inhibit fibrosis and scar formation in damaged tissue, thereby alleviating scarring-induced permanent ES ( Zein et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%